PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PUZZLE MATERI PECAHAN PADA MATA PELAJARAN MATEMATIKA KELAS II SD TIRANUS PONDOK KOPI JAKARTA TIMUR - Enjelika Enjelika; Rudi Ritonga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This study aims to develop a puzzle-based media on fraction material for second grade elementary school students by looking at the students' responses after carrying out learning activities using visual learning media. Puzzle-based media was developed to make it easier for students to understand fractional material. The object of research was the 2nd grade students of SD Tiranus Pondok Kopi with a total of 30 students. This type of research has used the Dick & Carrey development model. Puzzle-based media was tested for validation for material experts, design experts, and learning activity experts. Then small group trials, medium group tests, and large group trials were carried out. The results according to material experts were 86%, design experts were 82%, learning activity experts were 87%, small group trials were 7.3%, medium group trials were 80%, and large group trials were 91.6% with very decent category. Based on the research results, it can be concluded that the development of puzzle-based media on fraction material using the Dick and Carrey development model is feasible to use. The implication of this research is that it can create a fun learning atmosphere and provide enthusiasm and motivation to learn.